Bolaamphiphilic Bis-Dehydropeptide hydrogels as potential drug release systems - Amorim, Carolina (2021)
The self-assembly of nanometric structures from molecular building blocks is an effective way to make new functional materials for biological and technological applications. In this work, four symmetrical bolaamphiphiles based on dehydrodipeptides (phenylalanyldehydrophenylalanine and tyrosyldehydrophenylalanine) linked through phenyl or naphthyl linkers (terephthalic acid and 2,6-naphthalenedicarboxylic acid) were prepared, and their self-assembly properties were studied. The results showed that all compounds, with the exception of the bolaamphiphile of tyrosyldehydrophenylalanine and 2,6-naphthalene dicarboxylic acid, gave self-standing hydrogels with critical gelation concentrations of 0.3 wt % and 0.4 wt %, using a pH trigger. The self-assembly of these hydrogelators was investigated using STEM microscopy, which revealed a network of entangled fibers. According to rheology, the dehydrodipeptide bolaamphiphilic hydrogelators are viscoelastic materials with an elastic modulus G' that falls in the range of native tissue (0.37 kPa brain-4.5 kPa cartilage). In viability and proliferation studies, it was found that these compounds were non-toxic toward the human keratinocyte cell line, HaCaT. In sustained release assays, we studied the effects of the charge present on model drug compounds on the rate of cargo release from the hydrogel networks. Methylene blue (MB), methyl orange (MO), and ciprofloxacin were chosen as cationic, anionic, and overall neutral cargo, respectively. These studies have shown that the hydrogels provide a sustained release of methyl orange and ciprofloxacin, while methylene blue is retained by the hydrogel network.